The type-VI secretion system of the beneficial symbiont Vibrio fischeri - Guckes, Kirsten R.; Miyashiro, Tim I. (Microbiology, 2023)
The mutualistic symbiosis between the Hawaiian bobtail squid Euprymna scolopes and the marine bacterium   Vibrio fischeri   is a powerful experimental system for determining how intercellular interactions impact animal–bacterial associations. In nature, this symbiosis features multiple strains of   V. fischeri   within each adult animal, which indicates that different strains initially colonize each squid. Various studies have demonstrated that certain strains of   V. fischeri   possess a type-VI secretion system (T6SS), which can inhibit other strains from establishing symbiosis within the same host habitat. The T6SS is a bacterial melee weapon that enables a cell to kill adjacent cells by translocating toxic effectors via a lancet-like apparatus. This review describes the progress that has been made in understanding the factors that govern the structure and expression of the T6SS in   V. fischeri   and its effect on the symbiosis.
Keywords: Euprymna scolopes